Public health challenges for universal health coverage - Radha Madhab Tripathy (Wolters Kluwer Medknow Publications, 2014)
The effective functioning of any health system requires an efficient public health service. Every human being has the right to enjoy "the highest attainable standard of health," which can be fulfilled by giving every man an affordable and equitable health system he deserves and demands. In these years, complex health changes have complicated the situation in India. Most important gaps in the health care include an understanding of the burden of the disease and what leads to and causes ill health, the availability and use of appropriate technology in the management of disease, ill health and health systems that have an impact on service delivery. Universal Health Coverage (UHC) has the potential to increase economic growth, improve educational opportunities, reduce impoverishment and inequalities, and foster social cohesion. Steps taken for achieving UHC will address the public health challenges and vice versa.